Transformação digital na gestão de desempenho de servidores em estágio probatório de uma instituição pública - Albuquerque, Matheus Reisen de (2025)
The present research aims to analyze the possibilities for improving the performance management of Technical-Administrative Education (TAE) public servants in a probationary period, enabled by digital transformation. To this end, the study combines a systematic literature review, an analysis of the perceptions of staff at the Federal University of Espírito Santo (Ufes), and the proposal of practical strategies to enhance the evaluation process. The literature review resulted in a portfolio of articles that highlight the relationship between technological innovation and efficiency in public management. The data collected from Ufes staff members indicate that, although there is recognition of the potential of digital technologies to make evaluations fairer and more efficient, structural and cultural barriers still hinder their full adoption. The recent implementation of the Performance and Management Program (PGD) has proven to be a concrete opportunity for modernization by centralizing demands and promoting a results-oriented management approach. The study concludes that digital transformation can significantly improve the probationary period, provided it is guided by strategic planning, active involvement of managers and evaluators, and supported by investments in training and technological infrastructure. As a result, a technical report was developed, presenting digital transformation strategies to enhance the performance evaluation of TAE servants during the probationary period